Biochemical characterization of the two novel mgCas12a proteins from the human gut metagenome - Han Seong Kim; Dong-wook Kim; Sungjin Kim; Sunghwa Choe (Scientific Reports, 2022)
Abstract CRISPR/Cas9 and Cas12a belonging to the Class II CRISPR system are characterized by a single-component effector protein. Despite unique features of Cas12a like DNA cleavage with 5′ staggered ends and a single crRNA, Cas12a has not been adopted in biotechnological applications to the similar extent as Cas9. To better understand the CRISPR/Cas12 systems, we selected two candidates, designated mgCas12a-1 and mgCas12a-2, from an analysis of the human microbiome metagenome (mg) and provided biochemical characterization. These new Cas12a proteins shared about 37% identity in amino acid sequences and shared the same direct repeat sequences in the crRNA with FnCas12a from Francisella novicida. The purification yield of the recombinant proteins was up to 3.6-fold greater than that of FnCas12a. In cell-free DNA cleavage assays, both mgCas12a proteins showed the higher cleavage efficiencies when Mn2+ was provided with KCl (< 100 mM) than tested other divalent ions. They were able to tolerate ranges of pH points and temperature, and showed the highest cleavage efficiencies at pH 8.0 and 50 °C. In addition, mgCas12a proteins showed 51% less crRNA-independent and 56% less crRNA-dependent non-specific nuclease activity upon prolonged incubation than did FnCas12a. Considering their greater yield in protein preparation and reduced non-specific nuclease activity, our findings may expedite the use of Cas12a especially when genome editing needs to be practiced with the form of ribonucleoproteins.